Lung diffusing capacity for nitric oxide measured by two commercial devices: a randomised crossover comparison in healthy adults. Issue 3 (23rd August 2021) - Radtke, Thomas; de Groot, Quintin; Haile, Sarah R.; Maggi, Marion; Hsia, Connie C.W.; Dressel, Holger
In Europe, two commercial devices are available to measure combined single-breath diffusing capacity of the lung for nitric oxide ( D LNO ) and carbon monoxide ( D LCO ) in one manoeuvre. Reference values were derived by pooling datasets from both devices, but agreement between devices has not been established. We conducted a randomised crossover trial in 35 healthy adults (age 40.0±15.5 years, 51% female) to compare D LNO (primary end-point) between MasterScreen™ (Vyaire Medical, Mettawa, IL, USA) and HypAir (Medisoft, Dinant, Belgium) devices during a single visit under controlled conditions. Linear mixed models were used adjusting for device and period as fixed effects and random intercept for each participant. Difference in D LNO between HypAir and MasterScreen was 24.0 mL·min −1 ·mmHg −1 (95% CI 21.7–26.3). There was no difference in D LCO (−0.03 mL·min −1 ·mmHg −1, 95% CI −0.57–0.12) between devices while alveolar volume ( V A ) was higher on HypAir compared to MasterScreen™ (0.48 L, 95% CI 0.45–0.52). Disparity in the estimation of V A and the rate of NO uptake (KNO = D LNO / V A ) could explain the discrepancy in D LNO between devices. Disparity in the estimation of V A and the rate of CO uptake (KCO = D LCO / V A ) per unit of V A offset each other resulting in negligible discrepancy in D LCO between devices. Differences in methods of expiratory gas sampling and sensor specifications between devices likely explain these observations. These findings have important implications for derivation of D LNO reference values and comparison of results across studies. Until this issue is resolved, reference values, established on the respective devices, should be used for test interpretation. Large discrepancies between commercial devices to measure single-breath diffusing capacity of the lung for nitric oxide in healthy subjects caution against pooling or direct comparison of measurements obtained using different protocols and devices https://bit.ly/3vKyF7U